Synthesis of sn-2 docosahexaenoyl monoacylglycerol by mild enzymatic transesterification of docosahexaenoic acid ethyl ester and glycerol in a solvent-free system - Moreno-Pérez, Sonia; Luna, Pilar; Señoráns, Francisco J.; Guisán, José Manuel; Fernández-Lorente, Gloria (Cogent OA, 2016)
The enzymatic transesterification of docosahexaenoic acid (DHA) ethyl ester with glycerol was performed with several lipases in a solvent-free system and it involves the initial formation of sn-2 docosahexaenyl monoacylglyceride. This DHA derivative is highly relevant for improving the bioavailability of DHA and it has received increasing interest in the field of nutrition. Three commercial lipases, from Rhizomucor miehei (RML), Alcaligenes sp (QL), and Candida antarctica-fraction B (CALB) were tested. In certain cases (CALB), using an excess of DHA ethyl ester and high temperatures the transesterification reaction continues to the formation of triacylglycerides, but in other cases, sn-2 monoacylglyceride (2-MG) is the unique synthetic product even in the presence of high concentrations of DHA ethyl ester. At low temperatures (e.g. 37°C), RML derivatives synthesize only 2-MG in 15 min. These very mild conditions are very interesting for the thermal oxidative stability of the omega-3 fatty acid and for the thermal stability of the biocatalyst. Using Normal Phase HPLC-ELSD and accurate markers, the formation of the 2-MG was confirmed. This work was sponsored by the Spanish Ministry of Science and Innovation 223 [project number AGL-2009-07526], [project number BIO2012-36861]. Peer reviewed